Building Memory: Museums, Trauma, and the Aesthetics of Confrontation in Argentina. (September 2016) - Wilson, Kristi M.
The U.S.-backed Latin American military dictatorships of the 1970s and 1980s resulted in a lack of documentary evidence about the lives of thousands of political activists, intellectuals, union leaders, and everyday people who were tortured and disappeared by their own governments. In Argentina, people have attempted to come to terms with such horrific past events in a variety of ways that are neither static nor univocal. The dynamic process of memory building is influenced by ongoing political debates, shifting power dynamics, global markets, social movements, and a host of other factors such as justice policies. Spaces of memory and museums created in former clandestine centers of torture and disappearance bring to light a politics of truth that works against and reframes a history of silence through impunity. Parte del legado de las dictaduras militares latinoamericanas de los años 70 y 80 apo-yadas por los Estados Unidos es la carencia de pruebas documentales acerca de las vidas de miles de militantes políticos, intelectuales, líderes sindicales y gente común que fueron torturados y desaparecidos por sus propios gobiernos. En la Argentina, la gente ha tratado de lidiar con estos horribles hechos del pasado por medio de una variedad de formas que no son ni estáticas ni unívocas. El proceso dinámico de construir la memoria está influenciado por los debates políticos en curso, las cambiantes dinámicas de poder, los mercados globales, los movimientos sociales y una gama de otros factores tales como las políticas judiciales. Los espacios de la memoria y los museos creados en antiguos centros de tortura y desapariciones clandestinos como el ESMA y el Olimpo ponen de manifiesto una política de la verdad que de forma visual actúa en contra de una historia del silencio guiada por la impunidad y la redefine.